Cancer Care for the Whole Patient : Meeting Psychosocial Health Needs - Adler, Nancy E.; Page, Ann (Ann E. K.) (Online access: NCBI NCBI Bookshelf., 2008)
"Today, it is not possible to deliver high-quality cancer care without addressing patients' psychosocial health needs. All patients with cancer and their families should expect and recieve cancer care that ensures the provision of appropriate psychosocial health services through existing approaches, tools, and resources. This book recommends actions that oncology providers, health policy makers, educators, health insurers, health planners, researchers and research sponsors, and consumer advocates should undertake to ensure that this standard is met."--Jacket